ANALISIS SEMIOTIKA PADA COVER MAJALAH TEMPO EDISI TANGGAL 23 FEBRUARI-1 MARET 2015 - Marselin Diana; Retno Dyah Kusumastuti (Universitas Bunda Mulia, 2016)
This study was conducted to determine the meaning of what is entailed and what message to be conveyed to the magazine cover photo Tempo 23 February-1 March 2015. Data collection techniques are from raw data/archive, observation and documentation. By using political communication and theories of Charles Sander Pierce as the basic theory, this study reveales signs of icons, index, and symbol. Icon is a sign that is similar to the object it represents. Also, a sign has characteristics similar to what was intended. The index is a sign that has a causal relationship with what it represents. Symbol is a sign that convention, regulations or agreements agreed refers to the theory of meaning as a concept. Key Informants in this study is Eko Punto as Design Editor of Tempo magazine. From the cover of ‘Tempo’ magazine (23 February-1 March 2015 edition), featuring characters who are in the vortex of cases Budi Gunawan.Key words: Icon, Index, symbol